Hubungan Perilaku Hidup Bersih dan Sehat dengan Kadar Hemoglobin dan Feritin Serum pada Remaja Putri: The Association of Clean and Healthy Living Behavior along with Hemoglobin and Serum Ferritin Levels among Adolescent Girls - Suci Amalia; Sri Anna Marliyati; Mira Dewi; Dwinita Wikan Utami (Amerta Nutrition, 2023)
Background: Clean and healthy life behavior that is not appropriately implemented will cause various infectious diseases that trigger anemia. Islamic boarding schools have a significant role in instilling clean and healthy life behavior in students. Objectives: This study aimed to analyze the relationship between pure and healthy life behavior with hemoglobin and serum ferritin. Hemoglobin and serum ferritin are indicators for diagnosing iron deficiency anemia. Methods: The research design was a cross-sectional study conducted in January – February 2021 at the Al Falak Islamic Boarding School in Bogor. A total of 45 subjects were selected with inclusion criteria, namely students aged 12-20 years, in good health, and being in the dormitory during the study period, while the exclusion criteria were not being in the dormitory for more than two weeks. Anaemia data status was obtained by measuring hemoglobin and serum ferritin levels. Analysis of hemoglobin (Hb) levels used the Cyanmethemoglobin method, while the analysis of ferritin levels in serum samples used the Chemiluminescent Microparticle Immunoassay (CMIA) way. Analysis of the correlation between the dependent variable, namely hemoglobin and serum ferritin, and the independent variable, namely clean and healthy living behavior. Results: Based on the hemoglobin value, 37.8% of the subjects had anemia, while based on the serum ferritin value, as much as 51.1% of the subjects had low iron status. Behavior related to personal hygiene, conduct related to washing hands, and behavior associated with the cleanliness of the subject's residence was classified as good, respectively, at 55.6%, 57.8%, and 44.4%. There was a correlation between personal hygiene-related behavior with hemoglobin (p= 0.042) (r=0.305) and serum ferritin (p= 0.036) (r=0.313). Conclusions: Personal hygiene was related to hemoglobin and ferritin serum in adolescent girls due to maintaining a clean and healthy life in Islamic boarding schools, primarily associated with personal hygiene.